Cross-border Romanian Students Mobility in a Comparative Perspective - Andreea Vass (Romanian Journal of European Affairs, 2007)
Strategic management and greater policy coherence of Romania’s human resources is needed taking into account the interlinkages between demographic, education, labour market and migration flows changes. We focus in this paper on the high need of strengthening incentives for circular and repetitive migration of Romanian students. They represent the most relevant pool of the future-be skilled labour force. Overviewing the realities, it may come to no surprise that Romania has less higher education graduates than in EU. Nor that the expenses for the higher education represent nearly the same amount per capita as in the other EU countries, when adjusted with GDP. Nor that, according to international university rankings, Romanian universities score one of the lowest performance in Europe. Above all, today we risk that our best students migrate to western higher education schools without returning to their home country. A deep analysis of this phenomenon reveals an even harsher reality: the propensity of Romanian students to study abroad is even lower than in other neighbouring countries.